Effectiveness of building structure reinforcement to withstand earthquake loads with ETABS V.19 application (Case Study of Commercial Building "Butik Tanah Liek Pusako Mande”) - Silalahi, Juniman; Jolandina, Raudatul Fitri; Yusmar, Fajri; Syah, Nurhasan (CIVED, 2024)
This research addresses the vulnerability of commercial buildings to collapse during earthquakes due to inadequate structural design and identifies the structural weaknesses requiring reinforcement. The focus is on the use of steel bracing as a means to strengthen the structure. The specific case study is the commercial building "Butik Tanah Liek Pusako Mande" in Kota Padang. The research aims to determine whether reinforcing the building with additional steel bracing can enhance its stiffness during seismic events and identify the most effective type of steel bracing. The research methodology employs a quantitative descriptive approach, utilizing structural modeling in analysis software such as ETABS. The study involves analyzing displacements in buildings with and without steel bracing to quantify the effectiveness of the reinforcement. The results indicate that structures employing inverted V bracing achieve a maximum displacement of 9.515 mm in the X direction and 2.525 mm in the Y direction, resulting in a 67% reduction in drift for the X direction and 92% for the Y direction. In contrast, structures using X bracing show a maximum displacement of 30.635 mm in the X direction and 32.753 mm in the Y direction, indicating a 26% increase in drift for the X direction and 36% for the Y direction. The study concludes that inverted V bracing is more effective in reducing building drift compared to X bracing. In conclusion, the research findings suggest that commercial building "Butik Tanah Liek Pusako Mande" already possesses a structural stiffness compliant with standards. However, the addition of inverted V bracing proves effective in further reducing story drift, emphasizing its efficacy in enhancing the structural integrity of commercial buildings during seismic events.